Analyzing the Impact of Online Platforms on Gen Alpha’s Language Use - Mahmud, Aqshal Alifa; Azriani, Ayuniza; Purba, Tulus Maruli; Barus, Muhammad K. Gali (Universitas Pamulang, 2026)
This article analyzes how online platforms influence language use within Generation Alpha. With the rise of social media, Generation Alpha has become the first generation to have unrestricted social media exposure throughout their formative years. This unrestricted exposure raises questions about the developmental consequences of online platforms, particularly their impact on language development. This research utilized an online database and forthcoming social media discourse and text records for qualitative research. As language and communication use online are continually changing, the survey was designed to assess the use of the internet as a communication and language behavior tool within the social context of Gen Alpha participants. This multiple case study utilized descriptive social media discourse on the impact of social media on Gen Alpha participants’ language use and synthesized various case studies. The impact of social media predictive text tools and autocorrections and the influence of cyber-social discourse and cross-system social media tools on language development are influences to be considered. Overall, this research allows for a better understanding of the constant exposure and the development of linguistic styles and patterns within Gen Alpha.